Multi-field simulation and optimization of SiNx:H thin-film deposition by large-size tubular LF-PECVD. (1st November 2021) - Zhou, Jicheng; Huang, Jing; Liao, Jia; Guo, Yan; Zhao, Zengchao; Liang, Huiling
Highlights: A multi-physics coupling model is established based on COMSOL Multiphysics for tubular LF-PECVD. The effects of process parameters on coating SiNx :H are studied and the corresponding optimization results are obtained. A new gas transport structure is proposed for further simulation research. Abstract: In this paper, a coupled multi-physics field model based on the COMSOL Multiphysics platform is developed to simulate the deposition of SiNx :H thin films by LF-PECVD. The deposition process is simulated by combined analysis for the flow field, thermal field, chemical reaction field, and plasma field. The results have indicated that the temperature has the most significant effect on the deposition rate, the pressure and temperature are the major process parameter on the film uniformity. Through optimizing process parameters, the optimization range of the corresponding parameters is obtained. Compared with the original process, the coating rate of SiNx :H can be increased by 11.6%, and the uniformity performance can be controlled above 97%. By further optimizing the gas transport structure, the uniformity can be improved to 98.1%, the deposition rate can be increased by 1.44%. This paper provides a reference for solving the problems of low deposition rate and poor uniformity due to the increased size of tubular LF-PECVD equipment, which is conducive to improving the equipment capacity and the film quality, thus reducing the production cost and improving the performance of photovoltaic cells.